NETWORK STRATEGY AND CONFIGURATION OF THE PARTY SPACE - ERGASHEV, Bakhodyr (CENTRAL ASIA AND THE CAUCASUS, 2007)
We put country before party”—this post-election statement by Al Gore can be fully applied to the general mood in the Central Asian countries now busy strengthening their national security and transforming civil institutions. All of them have already acquired party constructs but have so far failed to create an adequate opposition to them. The local democracies’ strong sides are better seen in the context of the difficulties they are coping with and will probably overcome. There is a commonly shared opinion that the 2005 events in Kyrgyzstan delivered a heavy blow to the parties born in the 1990s: the majority of them are in an obvious crisis. Their ideas have lost their attractiveness,1 while they can no longer enlist new allies. “Network structures”2 or “metaaction,” “professional structures”—terms borrowed from specialists—are offered as an alternative to the “troubled political waters.” Sympathies with the network strategy have become synonymous with the complexity of the structure of relations among political actors (prominent public figures, heads of state structures, parties and other civil institutions, etc.), efficient means of human resources management, etc. This explains why the people in power, the strengthening business circles, and society, now aware of its integrity, are showing an ever-growing interest in this topic. It may be said without exaggeration that the network tradition is experiencing another period of high popularity.